Algebraic-delay differential systems, state-dependent delay, and temporal order of reactions - Walther, Hans-Otto; Justus Liebig University Giessen (My University, 2008)
Initial value problems for differential equations with delay.
Keywords: delay differential equation; state-dependent delay; white blood cells; temporal order; ddc:510